Addressing bullying through critical making. (29th October 2018) - Hughes, Janette; Morrison, Laura; Mamolo, Ami; Laffier, Jennifer; de Castell, Suzanne
Abstract: This paper explores how maker pedagogies helped middle school students develop transferable competencies, such as creativity, problem solving, self‐directed learning and citizenship skills. We offer an in‐depth look at how purposeful or critical making related to bullying awareness can help struggling students develop positive attitudes related to their roles as contributing members of a classroom community of learners.